Rare association of hyper IgE syndrome with cervical rib and natal teeth - Roshan Anupama; Janaki C; Parveen B; Gomathy N (Wolters Kluwer Medknow Publications, 2009)
Hyper IgE syndrome (HIES) is a rare immunodeficiency syndrome characterized by a triad of cutaneous abscesses, mostly caused by Staphylococus aureus; pneumonia; and raised IgE levels. Nonimmunological associations include course facial features, multiple bone fractures, joint hyperextensibility, and retained primary dentition. Patients require long-term antibiotic therapy. We report here a classical case of HIES with rare associations of natal teeth, bilateral cervical ribs, and conductive deafness. The patient was being treated with monteleukast and dapsone.